ASPEK NON-PERFORMING FINANCING DAN NON-PERFORMING QARDH PADA PRAKTIK PEMBIAYAAN DENGAN DANA ZAKAT - Muhammad Afdhal (Islamic Banking & Economic Law Studies (I-BEST), 2025)
The Financial Services Authority (OJK) has documented a rising trend in sharia financing over the last four years. This increase is evident in both the financing amounts and the financing health ratio. According to OJK's Sharia Banking Statistics (SPS) report, there has been an overall rise in financing alongside a reduction in Non-Performing Financing (NPF) from 2020 to 2023. BAZNAS Microfinance Desa (BMD) offers an alternative financing source. BMD, initiated by the National Amil Zakat Agency (BAZNAS), distributes productive zakat funds through a qardh loan financing model. The use of zakat funds for qardh loans reveals unique community-level dynamics, where zakat, as a tool for poverty reduction, is interpreted differently based on the fiqh perspectives adopted. This diversity affects the collectability of BMD financing, leading BMD to establish a new standard for the quality ratio of problematic financing debts, known as Non-Performing Qardh (NPQ).